Investigation of knowledge level about intrauterine device - Hediye Dagdeviren; Huseyin Cengiz; Bulent Babaoglu; Cihan Kaya; Keziban Dogan; Sukru Yildiz (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2013)
Objective: To investigate a level of knowledge about intrauterine device between females who were examined in our gynecology department. Metods: The study was conducted at Gynecology and Obstetric Department of Bakirkoy Dr. Sadi Konuk Teaching and Research Hospital between August 2012-November 2012. The study were included 189 patients who accepted to participate. For collecting data; a form of questionnaire was used which has gived information about the intrauterine device (IUD) and status of socio-demographic characteristics of the patients. The questionnaire were administered by the researchers in a separate room as a face-to-face interviews. SPSS 20.0 (SPSS Inc, Chicago, IL, USA) program was used for statistical analysis. Results: The mean age of the women in the study was 31.1 ± 9.9. 44.7% of women were not using any modern contraceptive method. IUD utilization rate was 3.2%. 1.6% of women had never heard IUD, %76.1 women heard copper IUD. 42% of respondents gave the wrong answer to IUD inserted into ovaries. Conclusion: The IUD which is a cheap, does not require patient compliance, and has high efficacy. In this study, we were not found a statisfically significant difference for answers to questions in patients with different socio-demographic characteristics. The main result of the study was; among all parcipitians ,even health care workers there was an important disability about level of knowledge for IUD. It is great importance the whole society, including health professionals must train about family planning. [Cukurova Med J 2013; 38(3.000): 440-445]